O038 Lower mean oxygen saturation in sleep is associated with worse cognitive performance in subjects with obstructive sleep apnoea. (7th October 2021) - Atkins, L; Zahnleiter, A; Georgeson, T; Szollosi, I; Coulson, E
Abstract: Introduction: Obstructive sleep apnoea (OSA) is a risk factor for cognitive impairment and has been associated with deficits in executive function, attention, and memory. Potential mechanisms of harm include sleep disruption and intermittent hypoxaemia. Our aim was to investigate whether the apnoea-hypopnoea index (AHI), arousal index (AI) and mean oxyhemoglobin saturation in sleep (mean SpO2 ) - conventional polysomnography (PSG) measures of respiratory disturbance, sleep fragmentation and nocturnal hypoxaemia respectively - were associated with worse cognitive performance in OSA subjects. Methods: In this cross-sectional analysis, 75 subjects with PSG-confirmed OSA (age: 66.1yrs ± 7.1yrs, male: 51%) were recruited from a hospital sleep clinic and had their cognitive profile screened via the Addenbrooke's Cognitive Examination – Revised (ACE-R). Linear regression was used to determine whether AHI, AI and mean SpO2 were associated with total ACE-R scores. Binary logistic regressions were then performed to determine whether increased severity of OSA (AHI ≥ 30 events/hour), sleep fragmentation (AI ≥ 30 events/hour), and hypoxaemia (mean SpO2 ≤ 92%) increased the likelihood that participants would have worse cognition (ACE-R score ≤ 88). Results: There was a modest positive association with mean SpO2 and ACE-R score (r² = 10.4%, p < 0.01). Similarly, logistic regression found only increased hypoxaemia (mean SpO2 ≤ 92%) to be associated with increased odds of worsened cognition (OR 3.00, 95% CI (1.090–8.254), p < 0.05). Discussion: OSA-induced hypoxaemia, and not sleep fragmentation or respiratory disturbance, was found to be most strongly associated with deficits in cognitive performance.